(untitled) (Journal of the College of Languages (JCL), 2021)
The article examines the definition of the verb in the form of the imperative mood (imperative) _ general information about the verb in Russian . A verb in Russian is one of the parts of speech that unify all parts of speech, expressing the meaning of action, movement, process in grammatical forms of time, type, mood, face and voice. The imperative mood is a grammatical feature of the verb expressed through several forms of the verb that urges someone to do things. In other words, imperative mood or (imperative) : - one of the single meaning of the form . The form of the imperative expresses a supplication, order, advice, etc. With the support of the imperative form, the communicator states his own desire , so that in this case another process should be carried out by someone else to fulfill the communicator desire. (go away!) , for example, Or, (Don’t go away!). В статье обьяснится определение глагола в форме повелительного наклонения (императива) _ общая сведения о глаголе на русском языке . Глаголом на русском языке является один из частей речи , который объединяет все слова , выражающий значение действия , движения, процесса в грамматических формах времени , вида , наклонения , лица и залога . Повелительное наклонение - это грамматическая особенность глагола , которая выражается через несколько форм глагола , которое кто-то побуждает совершенить дела . И другими словами Повелительное наклонение или (императив ) : - одино с значений группы наклонения . Форма императива выражает мольбу, приказ , совет и т. д . Со поддержкой императива сообщающий информирует об собственном желании , для того чтобы в таком случае либо другое процесс существовало осуществлено кем-в таком случае (Уходи!) либо , напротив , никак не проделывалось (Никак Не уходи!) .